An Analysis of University Students’ Academic Hardiness: Its Implication on Academic Achievement - Sari, Permata; Idris, Idriani; Siregar, Ilham Khairi (Universitas Islam Negeri Raden Intan Lampung, 2023)
Academic hardiness is crucial for students as it aids in coping with stress, improving academic performance, and fostering mental resilience. This study aimed to describe the level of academic hardiness among Gorontalo State University students as a basis for formulating programs by the Academic Services Unit. This descriptive study involved 136 students who were recruited using simple random sampling technique. Data were collected using an academic hardiness scale with a reliability level of 0.880. Data were analyzed using descriptive statistics, including frequency and central tendency calculations through IBM SPSS 22. The research result showed M=93.96 and SD=13.494. It also demonstrated that 92 students fell into the high category, 42 students into the moderate category, and 2 students into the low category. The results of this research provide a foundation for identifying students potentially in need of additional support in terms of academic hardiness and planning suitable interventions to be carried out by the Academic Services Unit at Gorontalo State University.